Accountability mechanisms for implementing a health financing option: the case of the basic health care provision fund (BHCPF) in Nigeria - Benjamin Uzochukwu; Emmanuel Onwujekwe; Chinyere Mbachu; Chinyere Okeke; Sassy Molyneux; Lucy Gilson (BMC, 2018)
Abstract Background The Nigerian National Health Act proposes a radical shift in health financing in Nigeria through the establishment of a fund - Basic Healthcare Provision Fund, (BHCPF). This Fund is intended to improve the functioning of primary health care in Nigeria. Key stakeholders at national, sub-national and local levels have raised concerns over the management of the BHCPF with respect to the roles of various stakeholders in ensuring accountability for its use, and the readiness of the implementers to manage this fund and achieve its objectives. This study explores the governance and accountability readiness of the different layers of implementation of the Fund; and it contributes to the generation of policy implementation guidelines around governance and accountability for the Fund. Methods National, state and LGA level respondents were interviewed using a semi structured tool. Respondents were purposively selected to reflect the different layers of implementation of primary health care and the levels of accountability. Different accountability layers and key stakeholders expected to implement the BHCPF are the Federal government (Federal Ministry of Health, NPHCDA, NHIS, Federal Ministry of Finance); the State government (State Ministry of Health, SPHCB, State Ministry of Finance, Ministry of Local Government); the Local government (Local Government Health Authorities); Health facilities (Health workers, Health facility committees (HFC) and External actors (Development partners and donors, CSOs, Community members). Results In general, the strategies for accountability encompass planning mechanisms, strong and transparent monitoring and supervision systems, and systematic reporting at different levels of the healthcare system. Non-state actors, particularly communities, must be empowered and engaged as instruments for ensuring external accountability at lower levels of implementation. New accountability strategies such as result-based or performance-based financing could be very valuable. Conclusion The key challenges to accountability identified should be addressed and these included trust, transparency and corruption in the health system, political interference at higher levels of government, poor data management, lack of political commitment from the State in relation to release of funds for health activities, poor motivation, mentorship, monitoring and supervision, weak financial management and accountability systems and weak capacity to implement suggested accountability mechanisms due to political interference with accountability structures.